Variability in sediment-water carbonate chemistry and bivalve abundance after bivalve settlement in Long Island Sound, Milford, Connecticut. (October 2018) - Meseck, Shannon L.; Mercaldo-Allen, Renee; Kuropat, Catherine; Clark, Paul; Goldberg, Ronald
Abstract: Cues that drive bivalve settlement and abundance in sediments are not well understood, but recent reports suggest that sediment carbonate chemistry may influence bivalve abundance. In 2013, we conducted field experiments to assess the relationship between porewater sediment carbonate chemistry (pH, alkalinity (At ), dissolved inorganic carbon (DIC)), grain size, and bivalve abundance throughout the July–September settlement period at two sites in Long Island Sound (LIS), CT. Two dominate bivalves species were present during the study period Mya arenaria and Nucula spp. Akaike's linear information criterion models, indicated 29% of the total community abundance was predicted by grain size, salinity, and pH. When using 2 weeks of data during the period of peak bivalve settlement, pH and phosphate concentrations accounted 44% of total bivalve community composition and 71% of Nucula spp. abundance with pH, phosphate, and silica. These results suggest that sediment carbonate chemistry may influence bivalve abundance in LIS. Highlights: Total bivalve community composition influenced by grain size, pH, alkalinity, and date Short term drivers of bivalve community settlement influenced by carbonate chemistry parameters Different bivalve species respond to different carbonate chemistry cues for settlement.